1987
DOI: 10.1111/j.1365-2621.1987.tb05887.x
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of High Bran Arabic Bread with Low Phytic Acid Content

Abstract: MATERIALS & METHODSIncubation of wheat bran at pH 5.2 and at a temperature of 55°C for various periods of time caused an increase in the levels of inorganic phosphorus and inositol phosphates and a simultaneous decrease in the level of phytic acid. When Arabic bread containing different levels of bran was prepared, up to 32% of the original phytic acid was lost during the process of bread preparation. Incorporation of wheat malt in the bread formula did not have any effect on phytic acid loss while incubation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

1990
1990
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…1981). The average reduction in phytic acid content in naan as a result of the baking and fermentation process was about 27%, which is in line with the findings of Daghter et al . (1987), who reported that during preparation of Arabic bread up to 32% of phytic acid is lost from flour containing different levels of bran.…”
Section: Resultssupporting
confidence: 91%
“…1981). The average reduction in phytic acid content in naan as a result of the baking and fermentation process was about 27%, which is in line with the findings of Daghter et al . (1987), who reported that during preparation of Arabic bread up to 32% of phytic acid is lost from flour containing different levels of bran.…”
Section: Resultssupporting
confidence: 91%
“…There are many forms of flat breads, namely, arabic bread, balady, barbari, bazlama, chapatti/capati/roti, gomme, lavosh/lavas, sangak, pide, pita, tanoor/tannouri/tandır bread, taftoon and yufka (Dagher et al . 1987; Qarooni et al .…”
Section: Introductionmentioning
confidence: 99%
“…1981). Accordingly, Daghter et al. (1987) reported that during preparation of Arabic bread up to 32% of phytic acid is lost from flour containing different levels of bran.…”
Section: Resultsmentioning
confidence: 99%
“…The cumulative losses of phytate phosphorus after fermentation, proofing and baking are reported to be 16, 19 and 22%, respectively (Tangkongchitr et al 1981). Accordingly, Daghter et al (1987) reported that during preparation of Arabic bread up to 32% of phytic acid is lost from flour containing different levels of bran. In all the treatments, no significant difference was found between Khabbazi and Nole breads in the molar ratio of phytic acid to Zn.…”
Section: Resultsmentioning
confidence: 99%